A modified CUSUM control chart for monitoring industrial processes. (21st May 2018) - Faisal, Muhammad; Zafar, Raja Fawad; Abbas, Nasir; Riaz, Muhammad; Mahmood, Tahir
Abstract: Control charts are the most popular tool of statistical process control for monitoring variety of processes. The detection ability of these control charts can be improved by introducing various transformations. In this study, we have enhanced the performance of CUSUM charts by introducing a link relative variable transformation technique. Link relative variable converts the original process variable in a form which is relative to its mean. So, the link relative represents the relative positioning of the observations. Average run length ( ARL ) is used to compare our technique with the previous studies. The comparison shows the overall good detection performance of our scheme for a span of shifts in the mean. A real‐world example from the electrical engineering process is also included to demonstrate the application of proposed control chart.